Flexibility and Competition in Food Manufacturing Industries - Christoph R. Weiss (Kiel University, Department of Food Economics and Consumption Studies, 1999)
This paper analyses the flexibility decision of firms. In particular we (a) ask whether the flexibility choice is influenced by market structure (concentration, market growth, ...), (b) compare the firms' actual choices with welfare maximising flexibility decisions (c) investigate the determinants of flexibility empirically for a panel of 4-digit U.S. manufacturing industries and (d) specifically analyse the flexibility decision in the U.S. food manufacturing industries. The paper is organised as follows. The following section 2 analyses the flexibility decision of firms theoretically. Section 3 discusses the empirical results from random effects models estimated on a panel of 299 4-digit U.S. manufacturing firms whereby specific attention is given to the situation in the food industry. Section 4 concludes.
Keywords: 330; Nahrungsmittelgewerbe; Fertigungstechnik; Technologiewahl; Anpassung; Wettbewerb; Spieltheorie; Schätzung; Produktivität; Flexibilität; Theorie; USA